Impact fracture strength applied to dental modeling materials - Sérgio Candido Dias; Marcos Ribeiro Moysés; José Augusto M. Agnelli; Gisseli Bertozzi Ávila; José Carlos Rabelo Ribeiro; Luciano José Pereira (Universidade Estadual de Campinas, 2016)
The aim of the present study was to analyze the impact fracture strength using plaster and resin modeling materials. The analysis was made using nine dies having plaster III bases and internal portion of laboratory-type addition silicone. Nine test specimens were produced of each following material: type IV Durone plaster, type IV Fuji Rock plaster, type IV Rock Plus plaster, type V Durone plaster, Epoxiglass 1504 epoxy resin, epoxy resin modified with diatomite and epoxy resin modified with diatomite. The tests were performed in a Ceast testing machine. At the moment of fracture, the machine recorded a value (Energy), using a formula to obtain the impact strength value in joules per meter. Statistical and variance analyses and Student's t test revealed that pure or silanized diatomite increased the impact fracture strength of models made of Epoxiglass 1504 epoxy resin and that silanizing the filler led to a further gain in impact fracture strength. The models made of Epoxiglass 1504 displayed greater impact fracture strength than those made of plaster types IV and V. No statistically significant differences were found among the analyzed plasters. Models prepared with epoxy resin displayed in general greater impact fracture strength than models made of plasters.